ANALYSIS OF SHALLOW GROUNDWATER QUALITY FOR DRINKING WATER NEEDS - Ahmad Iskandar; Nasarudin Nasarudin; Sudarwin Kamur; Yusuf Retq (Geographica: Science and Education Journal, 2022)
This research is based on water conditions in the Village of 19 November. There are some wells that do not meet the standards of clean water issued by the Ministry of Health of the Republic of Indonesia Number 492/Menkes/Per/IV/2010.  The purpose of this study was to determine the quality of shallow groundwater (wells) in 19 November Village. Based on regulations, the parameters measured consist of physical and chemical parameters.Physical parameters consist of odor, color, taste, temperature, and total dissolved solids, while chemical parameters consist of pH, BOD, and COD.  The data in this study were collected using observation techniques and laboratory analysis. Furthermore, the data is analyzed using descriptive statistics and the storet method. Based on the results of the analysis, it was found that the quality of shallow groundwater in 19 November Village was in the moderately polluted class and did not meet the standards. This is because the concentration of physical and chemical parameters has exceeded the set threshold.